2023
DOI: 10.1002/adhm.202300584
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell Culture within Perfusion Bioreactors Incorporating 3D‐Printed Scaffolds Enables Improved Extracellular Vesicle Yield with Preserved Bioactivity

Abstract: Extracellular vesicles (EVs) are implicated as promising therapeutics and drug delivery vehicles in various diseases. However, successful clinical translation will depend on the development of scalable biomanufacturing approaches, especially due to the documented low levels of intrinsic EV‐associated cargo that may necessitate repeated doses to achieve clinical benefit in certain applications. Thus, here the effects of a 3D‐printed scaffold‐perfusion bioreactor system are assessed on the production and bioacti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 67 publications
2
6
0
Order By: Relevance
“…Although 3D culture can increase the yield of SC-EVs and improve their activity in some aspects to enhance their effects, different 3D culture methods result in different biophysical factors such as shear stress and mechanical structure [ 143 ], which have a significant impact on the properties of EVs and lead to the production of EVs with large differences. However, there are many different 3D culture methods at present, and even the EVs produced by the same culture method still need to be further characterized.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although 3D culture can increase the yield of SC-EVs and improve their activity in some aspects to enhance their effects, different 3D culture methods result in different biophysical factors such as shear stress and mechanical structure [ 143 ], which have a significant impact on the properties of EVs and lead to the production of EVs with large differences. However, there are many different 3D culture methods at present, and even the EVs produced by the same culture method still need to be further characterized.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, UCMSCs cultured in hollow fiber bioreactor have been found to produce 7.5-fold higher amounts of exosomes compared to those produced by 2D culture flasks [ 142 ]. Additionally, Kronstadt et al reported that 3D printed scaffold-perfused bioreactor culture increased the yield of BMMSC-EVs by approximately 40- to 80-fold (depending on the measurement method) compared to conventional 2D cell culture [ 143 ]. The production of exosomes by hBMMSCs in 3D culture using hang-drop and poly (2-hydroxyethyl methacrylate) coating methods was also found to be approximately twofold and 2.4-fold higher, respectively, compared to 2D monolayer culture [ 144 ].…”
Section: Current Applications Of Evs Derived From 3d Cultured Scsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, the impact of a 3D-printed scaffold-perfusion bioreactor system on the production and bioactivity of EVs secreted by MSCs has been explored. Findings suggest that culture in a perfusion bioreactor can yield an approximate 40–80-fold increase in MSC EVs production, varying with the measurement technique, compared to traditional cell culture methods [ 79 ]. Although the application of MSC EVs produced via this system in liver disease has not yet been fully evaluated, the approach holds substantial potential for future therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%